MicroRNA profiles in a monkey testicular injury model induced by testicular hyperthermia. Issue 12 (12th April 2016) - Sakurai, Ken; Mikamoto, Kei; Shirai, Makoto; Iguchi, Takuma; Ito, Kazumi; Takasaki, Wataru; Mori, Kazuhiko
Abstract: To characterize microRNAs (miRNAs) involved in testicular toxicity in cynomolgus monkeys, miRNA profiles were investigated using next‐generation sequencing (NGS), microarray and reverse transcription‐quantitative real‐time‐PCR (RT‐qPCR) methods. First, to identify organ‐specific miRNAs, we compared the expression levels of miRNAs in the testes to those in representative organs (liver, heart, kidney, lung, spleen and small intestine) obtained from naïve mature male and female monkeys ( n = 2/sex) using NGS analysis. Consequently, miR‐34c‐5p, miR‐202‐5p, miR‐449a and miR‐508‐3p were identified to be testicular‐specific miRNAs in cynomolgus monkeys. Next, we investigated miRNA profiles after testicular–hyperthermia (TH) treatment to determine which miRNAs are involved in testicular injury. In this experiment, mature male monkeys were divided into groups with or without TH‐treatment ( n = 3/group) by immersion of the testes in a water bath at 43 °C for 30 min for 5 consecutive days. As a result, TH treatment induced testicular injury in all animals, which was characterized by decreased numbers of spermatocytes and spermatids. In a microarray analysis of the testis, 11 up‐regulated (>2.0 fold) and 13 down‐regulated (<0.5 fold) miRNAs were detected compared with those in the control animals. Interestingly, down‐regulated miRNAs included two testicular‐specific miRNAs, miR‐34c‐5p and miR‐449a, indicating their potential use as biomarkers for testicular toxicity. Furthermore, RT‐qPCR analysis revealed decreased expression levels of testicular miR‐34b‐5p and miR‐34c‐5p, which are enriched in meiotic cells, reflecting the decrease in pachytene spermatocytes and spermatids after TH treatment. These results provide valuable insights into the mechanism of testicular toxicity and potential translational biomarkers for testicular toxicity. Copyright © 2016 The Authors. Journal of Applied Toxicology published by John Wiley & Sons Ltd. Abstract : In this study, we identified 4 testicular‐specific miRNAs, miR‐34c‐5p, miR‐202‐5p, miR‐449a, and miR‐508‐3p based on next‐generation sequencing of miRNAs from representative organs obtained from naïve mature cynomolgus monkeys. Next, miRNAs were profiled in a model of testicular injury induced by testicular hyperthermia. Microarray and PCR analyses revealed down‐regulation of miR‐34c‐5p in the testis, which is enriched in meiotic cells, reflecting decreased numbers of pachytene spermatocytes and spermatids by the treatment.